Grist for the Sceptic's Mill: Rwanda and the African Peer Review Mechanism - JORDAAN, Eduard (Institutional Knowledge at Singapore Management University, 2007)
The article delves into the impact of the African Peer Review Mechanism (APRM) to Rwanda's achievement of greater democracy and respect for political freedom. It aims to show the improbability that the APRM can influence the country due to its insufficient ability and volition to pressure further democratization and respect for political rights on Rwandan government, the APRM's optimistic view of political governance, and the APR Heads of State Forum's ratification of a program of action discounting the issues of democracy and political freedom. The author stresses that the weaknesses of APRM may be attributed to the existing reduced authorization and the failure to enforce punishments on governments under review. The African peer review process is offered.